Toxicity and biomarkers of micro-plastic in aquatic environment: a review. (2nd January 2021) - Suman, Kamrul Hassan; Haque, Md Niamul; Uddin, Md Jamal; Begum, Most Shirina; Sikder, Mahmudul Hasan
Abstract: Microplastics (MPs; <5 mm) are found in all aquatic environments. Due to harmful impacts, MPs pose a great threat to the aquatic ecology. Therefore, this review aims to provide an overview of the risk, bioavailability, and toxicity of MPs in aquatic organisms. Various factors affecting MPs bioavailability and level of risks at cellular and molecular level on aquatic organisms are comprehensively discussed. More specifically biomarkers for antioxidant response (superoxide dismutase, catalase, glutathione peroxidase, reductase, and glutathione S-transferase), neurotoxic impairment (acetylcholinesterase), lysosomal activity alteration, and genotoxicity have been discussed in detail. Biomarkers are powerful tool in the monitoring programme, but the collection of literature on biomarkers for MPs is limited. Thus, here we demonstrate how to evaluate MPs impact, in monitoring programme, on organisms using biomarkers in aquatic environment. This review would broaden the existing knowledge on the toxic effect and biomarkers of MPs and offer research priorities for future studies.